UI/UX-ORIENTED DESIGN OF ONLINE MALL APPLICATION INTERFACES - Srirahayu, Agustina; Purweni, Mei; Rahmawati, Intan; Melani, Sulistyowati Dwiningsih (LPPM Universitas Duta Bangsa Surakarta, 2025)
The rapid growth of online shopping, particularly in the fashion industry, has highlighted the need for intuitive and user-friendly application interfaces. This study focuses on designing a UI/UX-oriented online mall application for Batik Solo Laweyan, an Indonesian batik product renowned for its unique quality and motifs. Despite the increasing demand for such products, many online shopping applications still struggle to provide an optimal user experience, with issues such as difficult navigation, insufficient product information, and complex payment processes. The research utilizes the Design Thinking approach, which includes the stages of Empathize, Define, Ideate, Prototype, and Test. This method ensures that the design process remains user-centered, with a clear focus on understanding user needs and addressing the challenges they face. Through interviews, surveys, and direct observation, the study identifies key issues such as poor navigation and lack of detailed product information. The design solutions developed focus on creating an intuitive interface, improving product visualization, enhancing the search functionality, and streamlining the payment process. The final prototype is tested for user feedback, allowing for continuous improvement to achieve a seamless and enjoyable online shopping experience for Batik Solo Laweyan products.